DETECTION AND MONITORING SYSTEM ON THE PACKAGE RECEIVING BOX - Sasmojo, Duta Widhya; Broto, Wisnu; Renaldi , Doni Chesa (Spektra: Jurnal Fisika dan Aplikasinya, 2021)
The package delivery system during this pandemic period require concerned health protocols. Receiving packages sometimes needs to be done even though there is no recipient. Here, the box for receiving goods has an important role. The goods receiving box must have security and ensure that the goods are received/placed in the box. In this case, it is necessary to detect the presence of objects in the box using a weight sensor, and a box locking motor is also needed. A push-button is needed when the package items are put into the box. The process of this activity can be monitored directly with the help of the Blynk application from a smartphone. The tests are carried out, and the push button signals to open the box. The weight sensor detects weight changes. The Blynk application will inform the smartphone that the object has been placed in the box from the weight change, and the system will lock the box again. The detection and monitoring system for goods on the box can work well.